PUTIN DAN KEDAULATAN ENERGI: KEPEMIMPINAN AUTARKI SEBAGAI BASIS STRATEGI PERTAHANAN NASIONAL - Roli Dewanto; Mandri Kartono, Tarsisius Susilo, Setiawan Arismunandar, Edi Wahyudi (INTELIGENSIA MEDIA, 2026)
Vladimir Putin’s autarkic leadership emphasizes Russia’s self-reliance in resources, particularly energy, as the foundation of its national defense strategy. Western geopolitical pressures such as NATO expansion and economic sanctions pushed Putin to weaponize energy as Russia’s strategic bargaining tool. This article examines how Putin’s energy sovereignty policies shaped Russia’s defense capabilities and explores lessons Indonesia can adopt in building a defense system based on strategic natural resources. Literature shows that Russia has leveraged its dominance in oil and gas exports for geopolitical influence, while domestically reinforcing state control over the energy sector and pursuing defense self-sufficiency despite sanctions. This study employs a qualitative case study approach, comparing Russia’s experience with Indonesia’s context. The analysis confirms that mastery of natural resources strengthens defense resilience; Russia financed its military modernization through energy windfalls and remained relatively resilient against embargoes through local innovation. For Indonesia, energy sovereignty is a prerequisite for long-term defense and must be integrated into national doctrine. However, Indonesia’s approach must adhere to Pancasila ethics utilizing resources for self- defense without weaponizing them for coercion. Key recommendations include cross-sector synergy (Energy–Defense) to secure strategic reserves for the armed forces, investment in new energy sources (biofuels, batteries) for military platforms, and strengthening resource-based defense industries. These steps will shape Indonesia’s 2045 defense posture into a resilient and self-reliant system, aligned with ethical values and global cooperation.